Exploring the impact of a sense of purpose on academic performance : Unveiling the moderating influence of time management - Arman, Hj Ahmad; Mohd Juraij, Abd Rani; Mohd Shahidan, Shaari; Ahmad Nizam, Che Kasim; Faiz, Masnan; Nur Salimah, Alias; Mohd Farid, Shamsudin (Elsevier Ltd., 2024)
This research examines the impact of having a sense of purpose on academic performance, focusing on the role of time management as a moderating factor. Surveys were distributed to the entire undergraduate student body across 20 public universities, encompassing a total target population of 626,222 undergraduates. Participants voluntarily participated in the study, leading to a dataset of 397 respondents for analysis. The study findings suggest a significant influence of a sense of purpose on academic performance. Additionally, the research highlights the crucial moderating role of time management in shaping the connection between a sense of purpose and academic success. These results contribute to a more comprehensive understanding of the complex dynamics within the academic environment and offer implications for developing targeted interventions to improve student success.